Twenty-Four-Hour Ambulatory Blood Pressure Variability Associated With Cerebral Small Vessel Disease MRI Burden and Its Progression in Inpatients With Cerebrovascular Disease - Fan, Yangyi; Hou, Chang; Peng, Li; Gao, Xuguang; Xu, Yan (Frontiers in Neurology, 2020)
Abstract: Background: Lacunar infarcts, white matter lesions, cerebral microbleed, enlarged perivascular space and brain atrophy are regarded as magnetic resonance imaging (MRI) manifestations of cerebral small vessel disease (cSVD). 24-hour blood pressure variability (BPV) has been reported to relate with cerebral small vessel disease, but the impact of 24-hour BPV on the total MRI cSVD burden and its progression in inpatients with cerebrovascular disease has not been investigated yet. Methods: We enrolled inpatients with cerebrovascular disease, who underwent the 24-hour ambulatory blood pressure monitoring (ABPM) and brain MRI scan at baseline and followed-up in our clinical information system. BPV was quantified by the calculation of standard deviation (SD), coefficient of variation (CV),weighed standard deviation (wSD) of blood pressure record. We evaluated the total cSVD score on baseline MRI and the MRI followed-up. The cSVD burden progression was estimated through the comparison of the total cSVD score on the two MRIs. Results: A total of 140 patients with an average age of 65.6 years were enrolled, 82.9% (116/140) of whom had one or more cSVD markers. After a median of 4.4 years follow-up, cSVD score progression were found in 50.7% (71/140) of the patients. Both SD and CV of SBP and DBP during 24-hour and daytime as well as the SBP wSD differed significantly among different total cSVD score groups. The SBP SD and CV during 24-hour and daytime, the SBP SD in nighttime, the DBP SD and CV during the daytime were significantly higher in the cSVD progression group. The SBP wSD and the DBP wSD were significantly higher in the cSVD progression group. Logistic regression analyses revealed daytime SBP SD and SBP wSD independent risk factors for total cSVD burden(daytime SBP SD: OR=1.628, 95% CI=1.105-2.398(per 5mmHg increase in SD), P=0.014; SBP wSD: OR=2.248, 95% CI=1.564-3.230(per 5mmHg increase in wSD), P＜0.001), and SBP wSD was a significant predictor for cSVD progression (OR=2.990, 95% CI=1.053-8.496(per 5mmHg increase in SD), P=0.040). Conclusion: Higher BPV significantly related to total cSVD burden.Daytime SBP SD and SBP wSD were independent risk factor for total cSVD burden, SBP wSD was an predictive factor for cSVD progression.